EXTREMOPHILE FISHES FROM EX-TIN MINE LAKE IN NIBUNG VILLAGE, CENTRAL BANGKA, BANGKA ISLAND - kurniawan, ardiansyah; Syarif, Ahmad Fahrul; Nurcahyono, Eka; Kurniawati, Febi; Putri, Zakia A; Silaen, Johannes OH; Andini, Anisah Meiga; Kurniawan, Andri (Universitas Cokroaminoto Palopo, 2025)
Tin mineral in Bangka Island has been mined since the 18th century until now. Tin mining has a positive impact on the economy in Bangka and Belitung, but has a negative impact on the environment with the formation of many new lakes called Kolong. Some ex-tin mine lake have extreme water quality with a low pH. One of them is a lake in Nibung Village, Central Bangka Regency, which has been identified as having an acidity of 3.37. Several fish species were found in the waters with high acidity values, namely Rasbora einthovenii, Trigonopoma pauciperforatum, Rasbora bankanensis, Betta edithae, Brevibora dorsiocellata, and Aplocheilus panchax. The six species can be categorized as extremophile fish. These fish have the ability to adapt to extreme environments so that they have the potential to be used as phylogeographic models and historical distributions.